ANALISIS IMPAS SEBAGAI DASAR PENGAMBILAN KEPUTUSAN MANAJEMEN DALAM PENENTUAN LUAS PODUKSI MINIMAL PADA INDUSTRI PEMINDANGAN IKAN LAUT DI DUSUN PAYANGAN WATU-ULO JEMBER - Amien Pudjanarso (STIE Mandala Jember, 2015)
This research was intended toanalys the minimum scale production of the sea fish preservation industry at Payangan village, watu-ulo, Jember, preventing the businessman in the sea fish preservation industry’s profit loss. Break even analized in this research are fixed cost, variable cost, price per unit, total revenue, total cost, and net sales. The population used in this researh are all of the businessman in the sea fish preservation industrial company by Payangan village, watu ulo (17 businessman). The data analysing method used in this research is break even point. The result show that scale of minimum production which businessman must achieves.